Chemostratigraphy and 40Ar/39Ar geochronology of Ventotene volcano (Pontian Islands, Tyrrhenian Sea): The missing link in the Quaternary potassic magmatism of central Italy - G.L. Cardello; A.M. Conte; M. Gaeta; B. Jicha; F. Lombardi; L. Monaco; S. Nomade; C. Perinelli; M. Petrelli; G. Sottili; D.M. Palladino (Quaternary Science Reviews, 2026)

High-temperature episyenites from late-Variscan Sàrrabus pluton (SE Sardinia, Italy) - F. Secchi; S. Naitza; A.M. Conte; G. Oggiano; M. Casalini; M. Kohút; T. Giovanardi (Lithos, 2026)

Morphological, petrographic and geochemical characterization of submarine mafic lavas and cones offshore Pantelleria island, Sicily Channel - Aida M. Conte; Cristina Perinelli; Daniele Casalbore; Marilena Calarco; Francesca Castorina; Fulvio Fonseca; Eleonora Martorelli (Journal of Volcanology and Geothermal Research, 2026)

Quantification of leaf photosynthetic traits in field conditions: Towards an efficient and reliable method for plant phenotyping and modelling ecophysiological processes - A. Conte; A. Carli; M. Haworth; G. Marino; V. Montesano; D. Danzi; G. Atzori; A.P.M. Fabbri; A. Daccache; R.M. Balestrini; M. Centritto (Agricultural and Forest Meteorology, 2026)

Growth modeling of autochthonous molds from the traditional Brazilian dry-cured loin “Socol”: Impact of the abiotic conditions - Denes do Rosario; Juliana X. Bissoli; Pedro H.A. Martins; Brenno A.S. Jacinto; Eniale M. Oliveira; Carlos A. Conte-Junior; Patrícia C. Bernardes (International Journal of Food Microbiology, 2026)

Exploring the molecular differentiation of sex chromosomes in Anastrepha fraterculus sp. 1 using comparative genomic hybridization (CGH) - M. Cecilia Giardini; Fabián H. Milla; Claudia A. Conte; Silvia B. Lanzavecchia; Mariela Nieves (Molecular Biology Reports, 2025)

CRISPR-Cas systems in combating antimicrobial resistance: which system to choose? A systematic review - Hannay Crystynah Almeida de Souza; Pedro Panzenhagen; Ana Beatriz Portes; Anamaria M. P. dos Santos; Juliana Fidelis; Carlos Adam Conte Junior (World Journal of Microbiology and Biotechnology, 2025)

A Chromosome Inversion Creates a Supergene for Sex and Colour in Lake Malawi Cichlids - Kristen A. Behrens; Soumya Jailwala; Frances E. Clark; Anne C. Meyer; Nikesh M. Kumar; Adrianus F. Konings; Reade B. Roberts; Matthew A. Conte; Jeffrey T. Streelman; Patrick T. McGrath; Thomas D. Kocher (Molecular Ecology, 2025)
Cichlid fishes have the highest rates of evolutionary turnover of sex chromosomes among vertebrates. Many large structural polymorphisms in the radiation of cichlids in Lake Malawi are associated with sex chromosomes and may also carry adaptive variation. Here, we investigate the structure and evolutionary history of an inversion polymorphism that includes both a ZW sex locus and an orange‐blotch colour polymorphism in the rock‐dwelling cichlid fishes of Lake Malawi. We use long‐read sequencing to characterise the sequence and breakpoints of the inversion. We quantify allele frequency differences across the inversion in population samples of the genera Metriaclima and Labeotropheus . We also examine expression differences of genes in the inversion. The simple inversion spans 7 Mb and is flanked by CACTA transposons that may have catalysed the rearrangement. The region includes ~600 genes, several of which show large differences in expression. Some of these genes are candidates for the sex and colour phenotypes. This inversion is an accessible model system for studying the role of structural polymorphisms and sex chromosome turnover in the adaptive radiation of cichlids in the lakes of East Africa.

Skeletal muscle alterations in Marfan syndrome: a systematic review - Audrei R. Santos; Rita M. S. Gutierrez; Tatiana E. Koike; Talita C. Conte; Caroline C. Real; Nicolas A. Dumont; Elen H. Miyabara (Journal of Muscle Research and Cell Motility, 2025)

Hazardous element inertisation in vitrified silicate ceramics: Effect of different matrices - S. Conte; C. Molinari; M. Ardit; L. Mantovani; M. Tribaudino; G. Cruciani; M. Dondi; C. Zanelli (Journal of Hazardous Materials, 2024)

New evidence of the Green Tuff deposits and post-caldera, recent explosive volcanic activity at Pantelleria volcano (Sicily Channel, Italy) recorded in near-vent marine areas - C. Romagnoli; C. Giglio; A.M. Conte; A. Cloke-Hayes; M. Garcia; G. Gasparotto; S. Benetti (Journal of Volcanology and Geothermal Research, 2024)

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

A second locus contributing to the differential expression of the blue sensitive opsin SWS2A in Lake Malawi cichlids - Sri Pratima Nandamuri; Jane E. Schulte; Miranda R. Yourick; Benjamin A. Sandkam; Kristen A. Behrens; Melissa M. Schreiner; Maya Dayanim; Garrett Sweatt; Matthew A. Conte; Scott A. Juntti; Karen L. Carleton (Hydrobiologia, 2023)

Torrefaction as a Chlorine Reduction Process of Brazilian Eucalyptus sp. for Use as Biofuel - Erica L. Romão; Jean M. da Silva; Nicolas V. dos Santos Luz; Rosa A. Conte (BioEnergy Research, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Traceological analysis of lithics from the Camel Site, al-Jawf, Saudi Arabia: an experimental approach to identifying mineral processing activities using silcrete tools - Yamandú H. Hilbert; Ignacio Clemente-Conte; Rémy Crassard; Guillaume Charloux; Maria Guagnin; Abdullah M. AlSharekh (Archaeological and Anthropological Sciences, 2022)
The Camel Site is in the north of Saudi Arabia in the province of al-Jawf. It is characterised by three decaying sandstone hillocks with life-sized 3D engravings (or reliefs) of camels and equids likely carved during later prehistory. A survey in the central area of the site identified clusters of flakes and other flintknapping remains in the lower areas between the sandstone spurs and larger silcrete tools directly underneath the animal depictions. Some of these tools presented abraded edges, possibly from prolonged contact with the soft and abrasive sandstone that constitutes the rock spurs where the animals were carved. Experiments were performed to test this hypothesis and have a reference collection for further traceological analysis. The chaine opératoire of the experimental engraving tools, from raw material procurement, tool manufacture and use, reuse and discard, was conducted with locally available materials comparable to the archaeological specimens. Specific experimental variables, including how the force was applied, in what direction the movement took place and the orientation of the stone tool during the experiment, were also recorded. Macro- and microscopic analyses of the experimental collection and a sample of archaeological artefacts seem to show that the ancient tools found on the surface were probably used to make the camelid and equid reliefs at the site.

Microencapsulated Lemongrass ( Cymbopogon flexuosus ) Essential Oil Supplementation on Quality and Stability of Silver Catfish Fillets during Frozen Storage - Cristine Rampelotto; Caroline S. Speroni; Lisiane Conte; Dirleise Pianesso; Isadora S. Machado; Renata F. Rodrigues; Natália M. Minuzzi; Taida J. Adorian; Bruna Klein; Roger Wagner; Bernardo Baldisserotto; Leila P. da Silva; et al. (Journal of Aquatic Food Product Technology, 2021)

Reaction kinetics formulation with explicit radiation absorption effects of the photo-Fenton degradation of paracetamol under natural pH conditions - Bárbara N. Giménez; Agustina V. Schenone; Orlando M. Alfano; Leandro O. Conte (Environmental Science and Pollution Research, 2021)

Micro-climatic investigation and particulate detection in indoor environments: the case of the historical museum of Bersaglieri in Rome - A. Marcelli; M. Sebastianelli; A. Conte; F. Lucci; G. Della Ventura (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)

Type three secretion system in Salmonella Typhimurium: the key to infection - Anamaria M. P. dos Santos; Rafaela G. Ferrari; Carlos A. Conte-Junior (Genes & Genomics, 2020)

Correction to: Inert gas narcosis in scuba diving, different gases different reactions - Monica Rocco; P. Pelaia; P. Di Benedetto; G. Conte; L. Maggi; S. Fiorelli; M. Mercieri; C. Balestra; R. A. De Blasi (European Journal of Applied Physiology, 2019)

Virulence Factors in Salmonella Typhimurium: The Sagacity of a Bacterium - Anamaria M. P. dos Santos; Rafaela G. Ferrari; Carlos A. Conte-Junior (Current Microbiology, 2019)

Inert gas narcosis in scuba diving, different gases different reactions - Monica Rocco; P. Pelaia; P. Di Benedetto; G. Conte; L. Maggi; S. Fiorelli; M. Mercieri; C. Balestra; R. A. De Blasi (European Journal of Applied Physiology, 2019)

Nosema ceranae in Apis mellifera : a 12 years postdetection perspective - Raquel Martín‐Hernández; Carolina Bartolomé; Nor Chejanovsky; Yves Le Conte; Anne Dalmon; Claudia Dussaubat; Pilar García‐Palencia; Aranzazu Meana; M. Alice Pinto; Victoria Soroker; Mariano Higes (Environmental Microbiology, 2018)
Summary Nosema ceranae is a hot topic in honey bee health as reflected by numerous papers published every year. This review presents an update of the knowledge generated in the last 12 years in the field of N. ceranae research, addressing the routes of transmission, population structure and genetic diversity. This includes description of how the infection modifies the honey bee's metabolism, the immune response and other vital functions. The effects on individual honey bees will have a direct impact on the colony by leading to losses in the adult's population. The absence of clear clinical signs could keep the infection unnoticed by the beekeeper for long periods. The influence of the environmental conditions, beekeeping practices, bee genetics and the interaction with pesticides and other pathogens will have a direct influence on the prognosis of the disease. This review is approached from the point of view of the Mediterranean countries where the professional beekeeping has a high representation and where this pathogen is reported as an important threat.

Preslaughter Anesthesia with Lippia alba Essential Oil Delays the Spoilage of Chilled Rhamdia quelen - Juliana C. Veit; Jaqueline Piccolo; Aline F. Scherer; Isadora S. Machado; Luana H. Maurer; Lisiane Conte; Bernardo Baldisserotto; Gessi Koakoski; Charlene C. Menezes; Vania L. Loro; Leonardo J. G. Barcellos; Berta M. Heinzmann; et al. (Journal of Aquatic Food Product Technology, 2018)

High Ca2+ Influx During Traumatic Brain Injury Leads to Caspase-1-Dependent Neuroinflammation and Cell Death - P. M. Abdul Muneer; Mathew Long; Adriano Andrea Conte; Vijayalakshmi Santhakumar; Bryan J. Pfister (Molecular Neurobiology, 2017)

Improvement in carbohydrate and phlorotannin extraction from Macrocystis pyrifera using carbohydrate active enzyme from marine Alternaria sp. as pretreatment - A. Leyton; R. Pezoa-Conte; P. Mäki-Arvela; J-P Mikkola; M. E Lienqueo (Journal of Applied Phycology, 2017)

Ferrioxalate-assisted solar photo-Fenton degradation of a herbicide at pH conditions close to neutrality - Leandro O. Conte; Agustina V. Schenone; Orlando M. Alfano (Environmental Science and Pollution Research, 2017)

Displacement of native Patagonian freshwater silverside populations (Odontesthes hatcheri, Atherinopsidae) by introgressive hybridization with introduced O. bonariensis - Eva C. Rueda; Kerry A. Mullaney; Cecilia Conte-Grand; Evelyn M. Habit; Víctor Cussac; Guillermo Ortí (Biological Invasions, 2017)

In situ remediation of contaminated marinesediment: an overview - G. Lofrano; G. Libralato; D. Minetto; S. De Gisi; F. Todaro; B. Conte; D. Calabrò; L. Quatraro; M. Notarnicola (Environmental Science and Pollution Research, 2017)

Tooth agenesis and orofacial clefting: genetic brothers in arms? - M. Phan; F. Conte; K. D. Khandelwal; C. W. Ockeloen; T. Bartzela; T. Kleefstra; H. van Bokhoven; M. Rubini; H. Zhou; C. E. L. Carels (Human Genetics, 2016)

The Ventotene Volcanic Ridge: a newly explored complex in the central Tyrrhenian Sea (Italy) - Marco Cuffaro; Eleonora Martorelli; Alessandro Bosman; Alessia Conti; Sabina Bigi; Filippo Muccini; Luca Cocchi; Marco Ligi; Giovanni Bortoluzzi; Davide Scrocca; Simonepietro Canese; Francesco L. Chiocci; et al. (Bulletin of Volcanology, 2016)

Clinical, Molecular, and Functional Characterization of CLCN1 Mutations in Three Families with Recessive Myotonia Congenita - Simona Portaro; Concetta Altamura; Norma Licata; Giulia M. Camerino; Paola Imbrici; Olimpia Musumeci; Carmelo Rodolico; Diana Conte Camerino; Antonio Toscano; Jean-François Desaphy (NeuroMolecular Medicine, 2015)

Total Mercury in Carnivorous Fish from Brazilian Southeast - M. S. Ferreira; A. N. Marques; R. O. R. Ribeiro; C. A. Conte; C. S. Carneiro; R. E. Santelli; A. S. Freire; S. C. São Clemente; E. T. Mársico (Bulletin of Environmental Contamination and Toxicology, 2015)

The antiatherogenic effect of bixin in hypercholesterolemic rabbits is associated to the improvement of lipid profile and to its antioxidant and anti-inflammatory effects - Sabrina Somacal; Cassieli G. Figueiredo; Andréia Quatrin; Amanda R. Ruviaro; Lisiane Conte; Paula R. Augusti; Miguel Roehrs; Ione T. Denardin; Jocieli Kasten; Marcelo L. da Veiga; Marta M. F. Duarte; Tatiana Emanuelli (Molecular and Cellular Biochemistry, 2015)

Photonic efficiency of the photodegradation of paracetamol in water by the photo-Fenton process - E. Yamal-Turbay; E. Ortega; L. O. Conte; M. Graells; H. D. Mansilla; O. M. Alfano; M. Pérez-Moya (Environmental Science and Pollution Research, 2015)

Propolis chemical composition and honeybee resistance against Varroa destructor - M. Popova; M. Reyes; Y. Le Conte; V. Bankova (Natural Product Research, 2014)

Adipose stromal/stem cells assist fat transplantation reducing necrosis and increasing graft performance - Maria Serena Piccinno; Elena Veronesi; Pietro Loschi; Marco Pignatti; Alba Murgia; Giulia Grisendi; Ilaria Castelli; Daniela Bernabei; Olivia Candini; Pierfranco Conte; Paolo Paolucci; Edwin M. Horwitz; et al. (Apoptosis, 2013)

Cephalic morphological variation in freshwater silversides Odontesthes hatcheri and Odontesthes bonariensis in Patagonia: introgression and ecological relationships - S. Crichigno; C. Conte‐Grand; M. Battini; V. Cussac (Journal of Fish Biology, 2013)
Based on geometric morphometrics and discriminant analysis, the percentage of silverside Odontesthes hatcheri and Odontesthes bonariensis individuals identified by a taxonomic key and misclassified by discriminant analysis was obtained and a negative correlation between the percentage of misclassified individuals of O. hatcheri and the distance to the nearest hatchery stocking silversides was found, suggesting a genetic introgression. Morphological analyses between species, between populations and within populations pointed to the same anatomical structures, suggesting a nested variation related to environmental cues such as availability of littoral shelter. The dependence between the cephalic morphology of O. hatcheri and body size would be in agreement with the trophic niche shifts of the species. Introgression adds a new threat to the already observed decline of populations of O. hatcheri and suggests that this species deserves particular consideration in terms of conservation guidelines.

Redox state of subcontinental lithospheric mantle and relationships with metasomatism: insights from spinel peridotites from northern Victoria Land (Antarctica) - Cristina Perinelli; Giovanni B. Andreozzi; Aida M. Conte; Roberta Oberti; Pietro Armienti (Contributions to Mineralogy and Petrology, 2012)

Plasmid-mediated fluoroquinolone resistance determinants in Escherichia coli from community uncomplicated urinary tract infection in an area of high prevalence of quinolone resistance - C. Longhi; M. P. Conte; M. Marazzato; V. Iebba; V. Totino; F. Santangelo; C. Gallinelli; L. Pallecchi; E. Riccobono; S. Schippa; A. Comanducci (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

In vitro optimization of retinoic acid–induced neuritogenesis and TH endogenous expression in human SH-SY5Y neuroblastoma cells by the antioxidant Trolox - Mario Luiz Conte da Frota Junior; André Simões Pires; Fares Zeidán-Chuliá; Ivi Juliana Bristot; Fernanda M. Lopes; Matheus Augusto de Bittencourt Pasquali; Alfeu Zanotto-Filho; Guilherme Antônio Behr; Fabio Klamt; Daniel Pens Gelain; José Cláudio Fonseca Moreira (Molecular and Cellular Biochemistry, 2011)

Correlation between cortical plasticity, motor learning and BDNF genotype in healthy subjects - P. Li Voti; A. Conte; A. Suppa; E. Iezzi; M. Bologna; M. S. Aniello; G. Defazio; J. C. Rothwell; Alfredo Berardelli (Experimental Brain Research, 2011)

Potential allelopathic activity of Sideritis italica (Miller) Greuter et Burdet essential oil - A. Basile; R. C. Cobianchi; D. Rigano; F. Senatore; M. Bruno; S. Rosselli; B. Conte; S. Sorbo (Plant Biosystems, 2011)

Phenotypic characterization and putative virulence factors of human, animal and environmental isolates of Plesiomonas shigelloides - A. Salerno; I. Čižnár; K. Krovacek; M. Conte; S. Dumontet; C. González-Rey; V. Pasquale (Folia Microbiologica, 2010)

Isolation and characterization of polymorphic microsatellites for the natural populations of barker frog Physalaemus cuvieri - M. Conte; L. J. Cançado; P. R. Laborda; M. I. Zucchi; G. V. Andrade; D. C. Rossa-Feres; S. Siqueira; A. P. Souza; S. M. Recco-Pimentel (Conservation Genetics, 2009)

Expression Profile and Distribution of Efhc1 Gene Transcript During Rodent Brain Development - Fábio F. Conte; Patrícia A. O. Ribeiro; Rafael B. Marchesini; Vinícius D. B. Pascoal; Joelcimar M. Silva; Amanda R. Oliveira; Rovílson Gilioli; Lourenço Sbragia; Jackson C. Bittencourt; Iscia Lopes-Cendes (Journal of Molecular Neuroscience, 2009)

Animal Welfare Labelling and the Approach of the European Union: An Overview on the Current Situation - Annamaria Passantino; F. Conte; M. Russo (Journal of Consumer Protection and Food Safety, 2008)

A single insemination intervention in the sow with barium alginate-encapsulated boar semen - M. Faustini; A. Riccardi; S. Villani; V. Russo; M. L. Torre; U. Conte; D. Vigo (Veterinary Research Communications, 2008)

The “in situ” expression of Human Leukocyte Antigen Class I antigens is not altered by cryopreservation in human arterial allografts - G. Pasquinelli; M. P. Pistillo; F. Ricci; M. Buzzi; P. L. Tazzari; L. Foroni; C. Manferdini; C. Ceccarelli; A. Stella; R. Conte (Cell and Tissue Banking, 2007)

Competence of Swine Oocytes Matured by Three-dimensional Gonadotropin-free Co-culture - E. Munari; A. Asti; C. Colombani; E. Benzoni; M. Faustini; M. L. Torre; A. Riccardi; S. Villani; L. Sesso; U. Conte; D. Vigo (Veterinary Research Communications, 2007)

Excitatory and inhibitory after-effects after repetitive magnetic transcranial stimulation (rTMS) in normal subjects - F. Gilio; A. Conte; N. Vanacore; V. Frasca; M. Inghilleri; A. Berardelli (Experimental Brain Research, 2007)

Antiinflammatory effects of natural tetranortriterpenoids isolated from Carapa guianensis Aublet on zymosan-induced arthritis in mice - C. Penido; F. P. Conte; M. S. S. Chagas; C. A. B. Rodrigues; J. F. G. Pereira; M. G. M. O. Henriques (Inflammation Research, 2006)

Topiramate and cortical excitability in humans: a study with repetitive transcranial magnetic stimulation - M. Inghilleri; F. Gilio; A. Conte; V. Frasca; C. Marini Bettolo; E. Iacovelli; B. Gregori; M. Prencipe; A. Berardelli (Experimental Brain Research, 2006)

Effects of repetitive transcranial magnetic stimulation in a patient with fixation-off sensitivity - O. Mecarelli; B. Gregori; F. Gilio; A. Conte; V. Frasca; N. Accornero; M. Inghilleri (Experimental Brain Research, 2006)

Synaptic potentiation induced by rTMS: effect of lidocaine infusion - M. Inghilleri; A. Conte; V. Frasca; F. Gilio; C. Lorenzano; A. Berardelli (Experimental Brain Research, 2005)

Antiapoptotic role of p38 mitogen activated protein kinase in Jurkat T cells and normal human T lymphocytes treated with 8-methoxypsoralen and ultraviolet-A radiation - A. Cappellini; P. L. Tazzari; I. Mantovani; A. M. Billi; C. Tassi; F. Ricci; R. Conte; A. M. Martelli (Apoptosis, 2005)

Antiepileptic drugs and cortical excitability: a study with repetitive transcranial stimulation - M. Inghilleri; A. Conte; V. Frasca; A. Curra’; F. Gilio; M. Manfredi; A. Berardelli (Experimental Brain Research, 2004)

Effects of some dicarboxylic acids on the association of dissolved humic substances - A. Piccolo; P. Conte; R. Spaccini; M. Chiarella (Biology and Fertility of Soils, 2003)

Animal Transmissible Spongiform Encephalopathies and Genetics - U. Agrimi; M. Conte; L. Morelli; M.A. Di Bari; G. Di Guardo; C. Ligios; G. Antonucci; G.M. Aufiero; N. Pozzato; F. Mutinelli; R. Nonno; G. Vaccari (Veterinary Research Communications, 2003)

Severe 5-fluorouracil toxicity associated with a marked alteration of pharmacokinetics of 5-fluorouracil and its catabolite 5-fluoro-5,6-dihydrouracil: a case report - Bocci G.; Danesi R.; Allegrini G.; Innocenti F.; A. Di Paolo; Falcone A.; Conte P.; M. Del Tacca (European Journal of Clinical Pharmacology, 2002)

Spread of electrical activity at cortical level after repetitive magnetic stimulation in normal subjects - Lorenzano C.; Gilio F.; Inghilleri M.; Conte A.; Fofi L.; Manfredi M.; Berardelli A. (Experimental Brain Research, 2002)

Petrological and geochemical characteristics of Plio-Pleistocene Volcanics from Ponza Island (Tyrrhenian Sea, Italy) - D. Dolfi; A. M. Conte (Mineralogy and Petrology, 2002)

Does the Spatial Distribution of the Parasitic Mite Varroa jacobsoni Oud. (Mesostigmata: Varroidae) in Worker Brood of Honey Bee Apis Mellifera L. (Hymenoptera: Apidae) Rely on an Aggregative Process? - M. Salvy; Y. Capowiez; Y. Le Conte; M. Salvy; J.-L. Clément (The Science of Nature, 1999)

Chronic Pulmonary Histoplasmosis in a Patient with a Recent History of Tuberculosis and Persistent Round Lung Lesions - M. A. Viviani; T. Masini; D. Conte; C. Trovato; R. Pometta (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Bactericidal effect of pefloxacin and fosfomycin againstPseudomonas aeruginosa in a rabbit endocarditis model with pharmacokinetics of pefloxacin in humans simulated in vivo - D. Bugnon; G. Potel; Y. Q. Xiong; J. Caillon; D. Navas; C. Gras; M. F. Kergueris; P. Le Conte; F. Jehl; D. Baron; H. Drugeon (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Signals of climatic change in the Central-Western Mediterranean basin - E. Piervitali; M. Colacino; M. Conte (Theoretical and Applied Climatology, 1997)

Elevated serum silicon levels in women with silicone gel breast implants - Suzanne S. Teuber; Robert L. Saunders; Georges M. Halpern; Robert F. Brucker; Victor Conte; Brian D. Goldman; Edward E. Winger; W. Graham Wood; M. Eric Gershwin (Biological Trace Element Research, 1995)